State estimation for coupled PDE systems using Modulation Functions - Pumaricra Rojas, David Raul (Pontificia Universidad Católica del Perú, 2022)
This master thesis is devoted to the state estimation of a particular form of PDE systems, coupled parabolic PDEs with spatial dependent coefficients. This form of PDEs represent some dynamic systems such as Tubular Reactors, Diffusion in lithium-ion cells and Diffusive Gradient in Thin Films sensor. Other methods for this problem use "Backstepping" observers, in which the estimation error system is transformed into another system that is stable, reducing the problem to calculate the Kernel functions making the transformation possible. In some cases this calculation is not simple, also the simulation in real time of the observer system, that is also a PDE, can be difficult. The method presented in this thesis uses the properties of the so-called Modulating Functions in order to estimate the states. The procedure con- sists of generating an orthonormal basis of functions that can represent the state as a combination of them. Then auxiliary systems are formed from the original systems with boundary conditions that help in the simplification of the problem. Resolving these auxiliary systems, result in the calculation of the Modulating kernels. All of these steps can be made offline and do not have to be repeated. The functions are used together with the orthonormal basis in the online part, that consists of an inte- gration of a combination of the kernel functions, inputs and outputs of the system in a time window. Finally, with a matrix multiplication the coefficients for the ba- sis expansion of the state can be obtained, resulting in the desired state estimation. The present method is tested in systems that resemble the forms of the dynamics of Tubular Reactors and the performance is compared to other methods.

Diese Masterarbeit widmet sich der Zustandsschätzung einer bestimmten Art von Systemen, gekoppelten partiellen Differenzialgleichungen mit raumabhängigen Ko- effizienten. Diese besondere Form von PDEs repräsentiert einige dynamische Sys- teme wie Röhrenreaktoren, Diffusion in Lithium-Ionen-Batterien und Gradienten in dünnen Schichten. Andere Methoden für dieses Problem benutzen "Backstep- ping" Beobachter, bei denen das Schätzfehlersystem in ein anderes stabiles System transformiert wird, wodurch das Problem reduziert wird, um die Kernfunktionen zu berechnen, die die Transformation ermöglichen. In manchen Fällen ist diese Berech- nung nicht einfach. Auch die Simulation in Echtzeit des Beobachters System, das auch eine PDE ist, kann sehr schwierig sein. Die in dieser Arbeit vorgestellte Meth- ode verwendet die Eigenschaften der sogenannten Modulationsfunktionen, um die Zustände zu schätzen. Das Verfahren besteht darin, eine Orthonormalbasis von Funktionen zu erzeugen können, die den Zustand als Kombination von ihnen repräsen- tieren, dann werden Hilfssysteme gebildet von dem ursprünglichen Systemen mit Randbedingungen, die bei der Vereinfachung helfen, von dem Problem. Das Au- flösen dieser Hilfssysteme ergibt die Berechnung der modulierende Kerne. Alle diese Schritte können offline durchgeführt und müssen nicht wiederholt werden. Die Funktionen werden zusammen mit der Orthonormalbasis im Online-Teil ver- wendet. Dieser Teil besteht aus einer Integration einer Kombination der Kernfunk- tionen, Eingaben und Ausgaben des Systems in einem Zeitfenster. Schließlich kön- nen die Koeffizienten zur Basiserweiterung mit einer Matrixmultiplikation berech- net werden, was zu der gewünschte Zustandsschätzung führt. Das Verfahren wird am Beispiel der Dynamik eines Rohreaktors getestet und die Ergebnisse werden mit anderen Methoden verglichen.
Keywords: Sistemas de control adaptable; Biorreactores; Simulación; https://purl.org/pe-repo/ocde/ford#2.02.03